Reflections on retrofits: Overcoming barriers to energy efficiency among the fuel poor in the United Kingdom. (November 2016) - Fylan, Fiona; Glew, David; Smith, Melanie; Johnston, David; Brooke-Peat, Matthew; Miles-Shenton, Dominic; Fletcher, Martin; Aloise-Young, Patricia; Gorse, Christopher
Abstract: To meet targets on fuel poverty, energy efficiency and carbon emissions existing homes need to be more energy efficient. We report the results of a participatory action research project to explore the challenges associated with energy efficiency retrofit programmes and ways to better implement future schemes. Six focus groups were held with 48 participants from a range of energy efficiency roles. Data were analysed thematically using the research question "What are the challenges presented by implementing energy efficiency retrofit programmes" . We identified four themes in the data: Funding mechanisms ; Predicting performance ; Installation; and People . Challenges include funding mechanisms for retrofit programmes resulting in insufficient time to plan, publicise, implement and evaluate a scheme and insufficient flexibility to specify the most appropriate intervention for individual homes. Site workers sometimes need to adapt retrofit designs because of insufficient detail from the designer and can equate quality of installation with quality of finish. Landlords and occupier behaviour can impact on the programme's success and there is a need for greater information on benefits for landlords and for energy behaviour change interventions run alongside retrofit programmes for occupiers. There is a need for outcome evaluations of retrofit schemes with the results shared with stakeholders.